PENGARUH LIFE REVIEW THERAPY TERHADAP HARGA DIRI RENDAH LANSIA DI KABUPATEN BUNGO - Narullita, Dewi (Jurnal Endurance, 2018)
Every one will experience age, where the elderly will arise changes as a result of the aging process. The aging process will cause both physical, psychosocial and spiritual issues. Psychosocial problems in the elderly one of them is low self-esteem. Low self-esteem problems in the elderly need to be addressed one of them with the action life review therapy. This purpose study is to determine the effect of life review therapy in the elderly who have low self-esteem in Social Home in Bungo Regency. Design of this study is quasi-experimental pretest and posttest with control group. Technic sampling by random sampling technique asignment as many as 40 people and classified into 20 peoples to intervention groups and 20 peoples to control group. The instrument used in this study is the Rosenberg Self Esteem Scale. The Analysis of paired t test obtained an average low self-esteem in the intervention group before therapy is given at 17.95 and after therapy is given at 10.20, with p value = 0.000. This results that is a significant difference in low self-esteem after being given a life review therapy in the intervention group. Therapy life review is recommended to overcome low self-esteem of the elderly living in Social Home.Setiap individu akan mengalami pertambahan usia, dimana lansia akan timbul perubahan-perubahan sebagai akibat proses penuaan. Proses penuaan tersebut akan menyebabkan masalah-masalah baik fisik, psikososial dan spiritual. Masalah psikososial pada lansia salah satunya adalah harga diri rendah.Â  Masalah harga diri rendah pada lansia perlu diatasi salah satunya dengan tindakanlife review tehrapy. Penelitian ini bertujuan untuk mengetahui pengaruh life review therapy pada lansia yang mengalami harga diri rendah di PSTW Kab.Bungo. Desain penelitian ini adalah quasi experiment pretest and posttest with control group. Pengambilan sampel dilakukan dengan teknik random sampling asignment yaitu sebanyak 40 orang dan diklasifikasikan menjadi 20 orang pada kelompok intervensi dan 20 orang pada kelompok kontrol. Instrumen yang digunakan dalam penelitian ini adalah Rosenberg Self Esteem Scale. Hasil uji paired t test didapatkan rata-rata harga diri rendah pada kelompok intervensi sebelum diberikan terapi sebesar 17,95 dan setelah diberikan terapi sebesar 10,20, dengan nilai p value = 0,000. Hal ini menunjukkan bahwa ada perbedaan yang bermakna harga diri rendah setelah diberikan terapi life review pada kelompok intervensi. Terapi life review direkomendasikan untuk mengatasi harga diri rendah pada lansia yang tinggal di PSTW